Innovation and regional development via the firm's core competence: Some recent evidence from North East England - Hamid R. Seddighi; S. Mathew (Journal of Innovation & Knowledge (JIK), 2020)
This paper examines the nature of linkages between core competence of a firm and key characteristics of its product/output and thus presents an alternative theoretical framework for innovation and regional development. Within this framework, it is the externally observable characteristics of what a firm produces, rather than its internal functions, that establishes whether a distinct core competence potentially exists, in order to operationalize it for R&D and innovation activities. To demonstrate potential applications of this framework, a literature-based- questionnaire was designed to collect primary data from 330 firms located in North East England, a peripheral region of the UK. Collected data were subjected to a detailed statistical analysis to estimate the conditional probability that a firm has a core competence, given the presence of one or more of its key output/product characteristics. Based on this approach, the paper presents a theoretical/empirical framework for the promotion of innovation via enhancement of a firm's core competence, and improvement in its output/product characteristics. This framework might be employed as a strategic management tool (1) by a firm to help in allocation of scarce resources for innovation and innovation management and (2) by regional policymakers for targeting and assisting firms in peripheral regions to enhance regional development via firms' innovation and exporting activities.
Keywords: 650; Firm's core competence; Innovation; North East England; Output/product characteristics; Strategic management